Ouvindo histórias: registros de som e memória da música popular - Campiotti, Julia Amad [UNESP]; Garcia, Tania da Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
"Listening to Stories: sound record and memory of Popular Music ", is an extension project of CEDAPHCenter of documentation and Historical research support of UNESP Franca/SP. It aims turn available to digital format the digitalized content of vinyl records and a collection already scanned, derived from donations of collectors. Along with the digitalization, cataloguing and organization to create a detailed database of all material, available in a digital online platform, which will facilitate the search and research, thus approaching this collection to the general public, also promoting the research in the area.

“Ouvindo Histórias: Registro de Som e Memória da Música Popular”, é um projeto de extensão do CEDAPH - Centro de Documentação e Apoio à Pesquisa Histórica UNESP Franca/SP. Objetiva disponibilizar em formato digital os conteúdos digitalizados de discos de vinil e também de um acervo já digitalizado, advindos de doações de colecionadores. Juntamente com a digitalização, catalogação e organização criar um banco de dados detalhado de todo o material, disponível em uma plataforma digital online, que facilitará a busca e a pesquisa, aproximando assim este acervo do público em geral, fomentando também a pesquisa na área.
Keywords: Vinyl; Scanning; Acquis; Vinil; Digitalização; Acervo